Background Noise Suppression of Optical Sectioning Structured Illumination Microscopy via Fourier Domain Reconstruction - Dang, Shipei; Qian, Jia; Peng, Tong; Bai, Chen; Min, Junwei; Wang, Haixia; Yao, Baoli; Dan, Dan (Frontiers in Physics, 2022)
Optical sectioning structured illumination microscopy (OS-SIM) has been attracting considerable interest in fast 3D microscopy. The reconstruction of optical sectioning images in the conventional method employs the root-mean-square (RMS) algorithm in the spatial domain, which is prone to residual background noise. To overcome this problem, we propose a Fourier domain based optical sectioning image reconstruction algorithm (termed Fourier-OS-SIM), which has an improved background noise suppression capability compared to the RMS algorithm. The experimental results verified the feasibility and the effectiveness of the algorithm. The improved performance of the Fourier-OS-SIM may find more applications in biomedical or industrial fields.